Inadequaç\~oes habitacionais e informalidade no mercado de habitaç\~ao brasileiro: Evidências empíricas a partir do Censo 2010 - Vanessa Gapriotti Nadalin (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This work seeks to describe the Brazilian formal and informal housing markets and the possible segmentations within these first two divisions. The main objective is to make explicit the similarities and differences, and the heterogeneities within each group. Considering inadequate housing features, there is a part of the formal market that is similar to the informal market. Just as there is a part of the informal market that is similar to the formal market, and therefore is free from more serious housing inadequacies. In this way, the work helps to answer an essential question: how much does informality influence the availability of adequate housing? The IBGE's concept of informal settlements, aglomerados subnormais (AGSN), was used as a proxy for informal settlements. This work innovates by describing the two markets based on information from the 2010 Census sample questionnaire, whose identification of belonging to a subnormal agglomeration was made inside the IBGE's confidential data center. Two important pieces of information available are those referring to the rent value and time spent commuting from home to work. Descriptive analyzes are performed using, among others, local spatial autocorrelation indicators (Lisa), scatter plots and binscatter regressions. A cluster analysis for census enumeration districts in the metropolises of Rio de Janeiro and S\~ao Paulo indicated that the very low-income market segment was found in the cluster that concentrated the most serious housing inadequacies, called no city. In both S\~ao Paulo and Rio de Janeiro, the vast majority of residents of no city are not in sectors classified, by IBGE, as AGSN.
10419/284905
Keywords: R31; O18; 330; Brazil; slums; informal settlements; Demographic Census; housing market